(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study uses a comparative qualitative approach to explore how English and Uzbek speakers express and conceptualize complex emotions such as fear, anger, sadness, and anxiety. Semantic analysis groups idioms by emotional domain and examines the metaphors (e.g., body parts, nature, containment) behind them. Structural analysis classifies idioms by grammatical type verbal, nominal, or sentential. By analyzing similarities and differences, the study explores both cognitive patterns and culture-related ways of expressing emotion. The findings from the research contribute to comparative phraseology, cross-cultural semantics, and affective linguistics, showing how language shapes emotional perception.